Perancangan Konten Digital Komunitas Ilustrasi Corat-Coret Sebagai Media Promosi - Idham Malik; Galih Mandala Putra; Yuni Awalaturrohmah Solihah (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2024)
In the era of rapid technological advancement, the utilization of digital content as a pivotal tool for advertising has become increasingly crucial. Digital content and illustration have emerged as essential elements in today's digital landscape, particularly in the realm of visual communication. The primary objective of this research is to create and disseminate digital content focused on educated illustration in the form of videos to enhance awareness within the Corat-Coret illustration community. To achieve this goal, the Integrated Marketing Communication (IMC) approach is employed to ensure that the targeting and alignment between the promotional elements used are appropriate, thereby ensuring a more consistent and effective message. This study leverages various software tools, including Capcut, Procreate, and Adobe Photoshop, to produce high-quality digital content. The final results of this research are presented in the form of engaging reels videos on Instagram platforms, as well as complementary physical media such as stickers, art prints, and keychains. By integrating these elements, the research aims to effectively attract and engage the target audience, thereby enhancing the overall marketing strategy